Extraction and utilization of active substances from edible fungi substrate and residue: A review. (1st January 2023) - Qin, Pufeng; Li, Tianyou; Liu, Chao; Liang, Yunshan; Sun, Haibo; Chai, Youzheng; Yang, Tingyu; Gong, Xiaomin; Wu, Zhibin
Graphical abstract: Highlights: The extraction method of fungus residue was systematically summarized. Role of extraction parameters on utilization of fungus residue was explored. The value-added of component in fungus residue was comprehensively discussed. The challenge and direction of utilizing fungus residue were put forward. Abstract: The expansion of the edible fungi industry has resulted in the production of large amounts of edible fungus residues, causing great pressure on environmental protection. Therefore, research on edible fungus residue utilization has become a controversial issue. Thus far, numerous efforts have been devoted to separate active substances from edible fungus substrates and residues for high application value utilization. Building upon this, the main methods for extracting active substances from edible mushroom residues are reviewed, and the mechanisms, influencing factors, and trade-offs of the various methods are analysed. Furthermore, the existing and possible directions of utilization of the extracted active substances are reviewed and discussed. Finally, challenges and prospects for the extraction and utilization of different substances in edible fungus residues are proposed. This review provides an effective strategy for protecting the ecological environment and promoting the sustainable development of human society.